Nephronophthisis: A Genetically Diverse Ciliopathy. (15th May 2011) - Simms, Roslyn J.; Hynes, Ann Marie; Eley, Lorraine; Sayer, John A.
Abstract : Nephronophthisis (NPHP) is an autosomal recessive cystic kidney disease and a leading genetic cause of established renal failure (ERF) in children and young adults. Early presenting symptoms in children with NPHP include polyuria, nocturia, or secondary enuresis, pointing to a urinary concentrating defect. Renal ultrasound typically shows normal kidney size with increased echogenicity and corticomedullary cysts. Importantly, NPHP is associated with extra renal manifestations in 10–15% of patients. The most frequent extrarenal association is retinal degeneration, leading to blindness. Increasingly, molecular genetic testing is being utilised to diagnose NPHP and avoid the need for a renal biopsy. In this paper, we discuss the latest understanding in the molecular and cellular pathogenesis of NPHP. We suggest an appropriate clinical management plan and screening programme for individuals with NPHP and their families.